Synergism of selective thermal denaturation and glycosylation improves quality characteristics of green soybean tofu. (2nd December 2022) - Liu, Yue; Sun, Dongxue; Ma, Yue; Mu, Sinan; Li, Hongyu; Zhang, Minghan; Liu, Xianqi; Wei, Xuan; Bilawal, Akhunzada; Tian, Bo; Jiang, Zhanmei
Abstract: BACKGROUND: Tofu is rich in nutrients and contains high‐quality protein. However, commercial tofu products usually have weak gel strength and low water holding capacity (WHC). In the present study, the effects of selective thermal denaturation (STD) time (0–20 min, 5‐min interval; 85 °C) and glycosylation (100 °C; 0, 10 and 20 g kg −1 glucose) on the quality characteristics of green soybean tofu were studied through by the evaluation method of the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) model for the best synergism condition of STD and glycosylation. RESULTS: Compared to STD or glycosylation, combination treatment of STD and glycosylation improved hardness, WHC, yield, protein and fat contents of green soybean tofu. Furthermore, the gel strength, WHC, yield, protein and fat contents of tofu was increased by 135.21%, 20.18%, 12.21%, 24.91%, 44.15% compared to untreated tofu. Meanwhile, synergistic treatment of STD and glycosylation significantly improved microstructure network structure of green soybean tofu and made it more homogeneous and denser. However, the green soybean tofu was faded and turned yellow under the combination of the STD and glycosylation. CONCLUSION: The results obtained through TOPSIS showed that the combination of thermal treatment (85 °C for 15 min) and glycosylation (20 g kg −1 glucose at 100 °C) had the greatest improvement in the characteristics of green soybean tofu. Hence, the combination treatment of STD and glycosylation should be useful for improving the quality characteristics of green soybean tofu and providing the technical references for industrial processing of tofu. © 2022 Society of Chemical Industry.